Food consumption patterns: findings from the Malaysian Adult Nutrition Survey(MANS) - Abdul Karim, Norimah; Mohd Yusof, Safiah; Hashim, Jamal Khair; Mohd Din, Siti Haslinda; Harun, Zuhaida; Saleh Hudin, Rohida; Salim, Fatimah; Mohd Ngadikin, Siti Norazlin; Poh, Bee Koon; Kandiah, Mirnalini; Mohd Shariff, Zalilah; Wan Muda, Wan Abdul Manan; et al. (Nutrition Society of Malaysia, 2008)
This study reports the food consumption patterns of adults aged 18 to 59 years in the Malaysian Adults Nutrition Survey (MANS) carried out between October 2002 and December 2003. A total of 6,742 subjects comprising 3,274 men and 3,468 women representing the northern, central , southern and east coast of Peninsular Malaysia as well as Sabah and Sarawak were interviewed. A semiquantitative food frequency questionnaire (FFQ) which consisted of 126 food items was used to evaluate the food consumption pattern (habitual food intake) of the respondents during the previous one-year period. The results demonstrate that nasi putih (cooked rice) was consumed by 97% of the population twice daily (average 2½ plates per day). Other food items consumed daily were marine fish, (one medium fish per day), green leafy vegetables (one cup per day) and sweetened condensed milk (three teaspoons per day. The mean frequencies for daily intake of rice, leafy vegetables, marine fish, local kuih, anchovy (ikan bilis) and biscuits were significantly higher among the rural compared to the urban adults. In contrast, more urban dwellers consumed chicken and eggs more frequently than their rural counterparts. More men than women consumed chicken and eggs more frequently. Malaysian adults showed a satisfactory habit of drinking plain water, with 99% drinking at least six glasses of plain water daily. Other beverages such as tea (47%), coffee (28%), chocolate-based drinks (23%) and cordial syrup (11%) were also consumed on daily basis, however, in a smaller proportion of the population. There were differences in the prevalence of daily consumption of foods when comparing urban and rural population, and also between men and women. The prevalence of daily consumption of marine fish among rural and urban adults was 51% and 34% respectively. For sweetened condensed milk, men and women consumed 43% and 28% respectively; however, more women drank full cream milk than men. Between the age groups, 21% of adults below 20 years old consumed chicken at least once a day, while this pattern of intake was not shown in the older age groups. Our findings show that adults, aged 50 to 59 years old, had the highest prevalence of daily consumption of full cream milk with 24% while those aged 18 to 19 years old had the lowest prevalence of daily consumption at 15%. The food consumption pattern of Malaysian adults appears to be satisfactory. However, some changes in food habits are recommended especially in substituting the less wholesome sweetened condensed milk with the more nutritious full cream or skimmed milk.